2019
DOI: 10.1016/j.apsusc.2019.143634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the passive layer on ferrite and austenite phases of super duplex stainless steel

Abstract: In this study, we report on a combined microscopic, analytical and electrochemical characterization of the nanoscopic passive layer on a tungsten-molybdenum-containing super duplex stainless steel. We used scanning transmission electron microscopy/energy dispersive Xray spectroscopy, scanning Kelvin probe force microscopy, scanning tunneling spectroscopy, and Mott-Schottky electrochemical impedance spectroscopy analysis to correlate the local chemical composition and electronic properties of passive layers on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…This observation is in line with the uniform corrosion observed in 7 M LiCl solution at 60 • C of UNS S32750 in this work. Nevertheless, the selective dissolution of ferrite observed for UNS S39274 is not in line with the SKPFM results obtained by Rahimi et al [41], where ferrite showed a nobler behavior than austenite. On the other hand, selective dissolution of ferrite of SDSS was observed by Långberg et al [42] as the data obtained by synchrotron XRR, XRF, and XRD showed a higher dissolution quantity of Fe from ferrite than austenite.…”
Section: Role Of W In Crevice-like-solutionscontrasting
confidence: 83%
See 1 more Smart Citation
“…This observation is in line with the uniform corrosion observed in 7 M LiCl solution at 60 • C of UNS S32750 in this work. Nevertheless, the selective dissolution of ferrite observed for UNS S39274 is not in line with the SKPFM results obtained by Rahimi et al [41], where ferrite showed a nobler behavior than austenite. On the other hand, selective dissolution of ferrite of SDSS was observed by Långberg et al [42] as the data obtained by synchrotron XRR, XRF, and XRD showed a higher dissolution quantity of Fe from ferrite than austenite.…”
Section: Role Of W In Crevice-like-solutionscontrasting
confidence: 83%
“…This dissolution order fits the behavior seen for UNS S32750 in Table 2, where the surface was enriched in Ni and Mo and depleted in Cr and, especially, Fe. However, Rahimi et al [41] stated that W promotes the stability of Mo, Cr and Fe. This statement can explain why the W-rich material experimented no Cr impoverishment and a much lower dissolution of Fe than the W-free material.…”
Section: Role Of W In Crevice-like-solutionsmentioning
confidence: 99%
“…A lower Volta potential indicates a higher relative corrosion tendency, that is, these low-potential areas are preferential sites for nucleation of pitting corrosion. [41] These results illustrated that the TiN has a F I G U R E 7 Scanning Kelvin probe force microscopy maps of the TiN in duplex stainless steel higher corrosion tendency due to the microscopic galvanic and heterogeneous effect between TiN and matrix. The misfit of the large TiN in the structure adversely affected the corrosion resistance of the duplex stainless steel with excessive alloy element of Ti.…”
Section: Effect Of Ti Addition On the Corrosion Resistancementioning
confidence: 88%
“…In this study, a bath of 30% nitric acid was used. During the process of passivation, the chromium contained in the materials is primarily oxidized into the form of chromium trioxide which acts as a barrier on the free surface [28]. The composition of a passive layer formed on the surface of the implant spontaneously if exposed to air is very similar to the passivation layer formed on the surface chemically, the main difference is its thickness.…”
Section: Discussionmentioning
confidence: 99%